Experimental energy and exergy analysis of a double-flow solar air heater having different obstacles on absorber plates - Esen, Hikmet (Pergamon-Elsevier Science Ltd, 2008)
This paper presents an experimental energy and exergy analysis for a novel flat plate solar air heater (SAH) with several obstacles and without obstacles. For increasing the available heat-transfer area may be achieved if air is flowing simultaneously and separately over and under the different obstacle absorbing plates, instead of only flowing either over or under the different obstacle absorbing plates, leading to improved collector efficiency. The measured parameters were the inlet and outlet temperatures, the absorbing plate temperatures. the ambient temperature, and the solar radiation. Further, the measurements were performed at different values of mass flow rate of air and different levels of absorbing plates in flow channel duct. After the analysis of the results, the optimal value of efficiency is middle level of absorbing plate in flow channel duct for all operating conditions and the double-flow collector supplied with obstacles appears significantly better than that without obstacles. At the end of this study, the exergy relations are delivered for different SAHs. The results show that the largest irreversibility is occurring at the flat plate (without obstacles) collector in which collector efficiency is smallest. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: solar air heater; experimental; exergy analysis; double-flow; obstacles; thermal efficiency